Optimization of heterogeneous interconnection transmission based on impedance matching for 3-D IC high-frequency application. (January 2022) - Yin, Xiangkun; Lu, Jingyu; Wang, Fengjuan
Abstract: Through-silicon via (TSV) is becoming an optimizing interconnection to realize high density, three-dimensional (3-D) integration system. However, its high-frequency application is limited due to the serious parasitic effect, impedance mismatch, crosstalk and so on. In this work, the impedance mismatch characteristic between heterogeneous interconnection is analyzed, modeled and simulated. Interdigital-capacitor based impedance matching structure and a corresponding analytical method are proposed for 3-D IC broadband application. The results obtained from the model and the finite element method (FEM) simulation show that the structure can effectively decrease the transmission losses: the S 21 of a matched circuit is improved from −1.4 dB to −0.25 dB at 60 GHz. Furthermore, a polynomial fitting algorithm is proposed to achieve quick and accurate impedance matching and to meet the needs of different application frequency and insertion losses in microwave interconnection systems.